Need Analysis On Developing Arabic Language M- Learning Basic Level During Covid-19 - Yahaya, Mohd Firdaus; Halim, Zulazhan Ab.; Sahrir, Muhammad Sabri; Hamid, Mohd Fauzi Abdul (The journal of contemporary issues in business and government, 2021)
The Coronavirus (or Covid-19), which spread in early 2020, has resulted in a change of learning mode in known educational institutions where there is a shift from face-to-face to online learning. This study was conducted to identify the needs for developing mobile learning (m-learning) modules at the basic level for Arabic language among students as well as identifying the level of student acceptance for m-learning. A set of questionnaires was distributed to the respondents to identify the need for developing such m-learning. The data obtained were then analyzed using SPSS software and interpreted based on the total mean score and standard deviation. The study found that the respondents saw a great need at developing a module for basic level Arabic m-learning and were positive to use the latest technology in the learning process. This study proposes learning strategies and activities through m-learning that can be used throughout this pandemic in order to continue online teaching and learning sessions.